Arahan Pengembangan Hutan Rakyat untuk Penanganan Lahan Kritis di Kabupaten Sukabumi, Provinsi Jawa Barat - Dharma Agustinus Sirait; Widiatmaka Widiatmaka; Omo Rusdiana (Diponegoro University, 2021)
Community forest plants can be an alternative fulfillment of raw material for the timber industry. While Sukabumi Regency is region with the largest area in West Java Province, so it the potential for development of community forest plants. This study wants to find the availability of land for development community forest plants, analyzing the suitability of community forest plantations, and formulating direction for development community forest plants in Sukabumi Regency. The study was conducted in Sukabumi Regency, which began in February-August 2019. The data used is the weight of each criteria for suitability of community forest plants from experts, data Land Map Units from BBSDLP, land use maps, RTRW maps, forest area maps, and land licensing. The method used is spatial analysis for determining available land, Analytical Hierarchy Process (AHP) for determining criteria weights, Multi Criteria Evaluation (MCE) for analyzing land suitability, and spatial analysis for determining development priority directions. The results showed that availability land for development of community forest plants in Sukabumi Regency was 57,786 hectares. The available land area in Sukabumi Regency which is classified as suitable (S1, S2, S3) i.e 57%. The development of community forest plants is directed at priority 1, which is an 83%.